Association between herpes zoster ophthalmicus and the risk of corneal ulcer - Weng, Shih-Feng; Chang, Yuh-Shin; Wang, Jhi-Joung; Jan, Han-Yi; Chen, Jiun-Yi; Tseng, Sung-Huei; Jan, Ren-Long (Frontiers in Medicine, 2025)
IntroductionHerpes zoster ophthalmicus (HZO) is a serious condition resulting from the reactivation of the varicella-zoster virus, affecting the ophthalmic branch of the trigeminal nerve. In HZO, exposure keratopathy can lead to a range of ocular surface disorders, including superficial punctate keratitis and disruption of the ocular surface barrier, thereby increasing the risk of infectious corneal ulcers. This study, therefore, aimed to investigate the risk of corneal ulceration in patients with HZO.Materials and methodsThis nationwide, population-based, retrospective, matched-cohort study included 44,317 newly diagnosed patients with HZO, identified using the International Classification of Diseases, Ninth Revision, Clinical Modification, and selected from the Taiwan National Health Insurance Research Database. The control group, matched for age, sex, and potential comorbidities, included 132,951 patients without HZO selected from the Taiwan Longitudinal Health Insurance Database 2000. Patient data were collected between 1 January 2004 and 31 December 2011 with both groups tracked from the index date until December 2013. The incidence and risk of corneal ulcers were compared between the groups. Cox proportional hazards regression analysis was used to calculate the adjusted hazard ratio for corneal ulcer development, while the cumulative incidence rate of corneal ulcers was estimated using Kaplan–Meier analysis.ResultsA total of 1,374 patients with HZO and 938 controls developed corneal ulcers during the follow-up period. The incidence rate of corneal ulcer was 4.59 times [95% confidence interval (CI) = 4.23–4.99; p < 0.0001] higher in patients than in controls. After adjusting for potential confounders, including diabetes mellitus, atopy trait, chronic renal disease, ocular allergic conditions, human immunodeficiency virus infection, and contact lens wearing, patients with HZO were 4.53 times more likely to develop a corneal ulcer in total cohort (adjusted HR, 4.53; 95% CI = 4.17–4.93; p < 0.05).ConclusionPatients with HZO are at an increased risk of developing corneal ulcers and should be appropriately counseled regarding this risk.